2005
DOI: 10.1136/jcp.2004.020347
|View full text |Cite
|
Sign up to set email alerts
|

Expression and gene amplification of primary (A, B1, D1, D3, and E) and secondary (C and H) cyclins in colon adenocarcinomas and correlation with patient outcome

Abstract: Background/Aims: Deregulation of cell cycle control is a hallmark of cancer. The primary cyclins (A, B1, D1, D3, and E) are crucial for cell cycle progression. Secondary cyclins (C and H) have putative indirect effects on cell cycle progression and have not previously been evaluated in colon cancer. This study examined cyclin protein expression and gene amplification in colon adenocarcinoma and the correlation with patient outcome. Methods: Immunohistochemistry and real time quantitative polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 43 publications
5
74
0
2
Order By: Relevance
“…The findings of Wang et al support the theory of overexpression of cyclin E in CRC without a significant correlation with clinical and pathological characteristics (33). Bondi et al did not identify a significant correlation between cyclin E expression and gene amplification in primary colon adenocarcinomas and clinical outcome (34). Cyclin E was found to be higher in rectal cancer compared with colon cancer in a study from Norway (35).…”
Section: A B Csupporting
confidence: 70%
“…The findings of Wang et al support the theory of overexpression of cyclin E in CRC without a significant correlation with clinical and pathological characteristics (33). Bondi et al did not identify a significant correlation between cyclin E expression and gene amplification in primary colon adenocarcinomas and clinical outcome (34). Cyclin E was found to be higher in rectal cancer compared with colon cancer in a study from Norway (35).…”
Section: A B Csupporting
confidence: 70%
“…The findings of Bondi et al are congruent with the report of low expression of cyclin A, showing a significant association with unfavorable prognosis in colon cancer. 18 It has been suggested that a decrease, rather than increase, in cyclin A in cells promotes tumorigenesis, and once the tumor has developed, high levels of cyclin A indicate the high proliferation rate, 2 which could explain this inconsistency of those studies. Only a few reports concerning cyclin A expression in gastric cancer have been made, but no correlation with survival was evident.…”
Section: Discussionmentioning
confidence: 74%
“…A value less than 5% was considered negative, and one equal to or greater than 5% was considered positive. 17,18 Cyclin A immunostaining was scored in a consensus manner without preliminary knowledge of clinical data (J.M. and S.N.).…”
Section: Scoringmentioning
confidence: 99%
“…Little is known about the regulation of the CAK complex though cyclin H [24,25]. Immunohistochemistry and real time quantitative polymerase chain reaction were used to determine cyclin expression and gene amplification in 219 tumors; the results indicated that cyclin H was overexpressed in all tumors [26][27][28]. These results mentioned above indicated that several biomarkers for cancer diagnosis can be found in a 2D-PAGE gel according to the approach describes hereto.…”
Section: Differential Protein Identificationmentioning
confidence: 79%